Pope Leo XIV : the biography - Allen, Elise Ann (Image, an imprint of the Penguin Random House Christian Publishing Group, 2026)
"From Elise Ann Allen, journalist and Rome correspondent for Crux comes this intimate biography of Pope Leo XIV, including his first-ever public interview as Pope"-- Provided by publisher.